The Effect of Complete The Story Game towards Students’ Vocabulary Mastery - Nurchurifiani, Eva; Febriyanti, Febriyanti; Jumiati, Jumiati (STKIP PGRI Bandar Lampung, 2023)
The research was conducted at SD Negeri 2 Labuhan Ratu, Bandar Lampung in 2022/2023 academic year. In this research the writer used experimental method. It consist of two classes, they were experimental class and control class. The population of this research was the students at the first semester of the fifth grade at SD Negeri 2 Labuhan Ratu, Bandar Lampung. The population consisted of 66 students from three classes. The sample of this research was VA and VB. The writer used cluster random sampling technique. In the data collecting technique the writer used test, kind of the test is multiple choice. To prove the hypothesis that there is positive and significant effect of Complete the Story Game towards students’ vocabulary mastery, the writer used ttest formula. The result of this research showed that the average score of students’ vocabulary mastery in experimental class (71.3) was higher than the students’ vocabulary mastery in control class (50.17). Then, the writer got the result of ttest was higher than ttable with significance level 5% (7.57>1.68). It means that the writer proved the hypothesis that there was significant effect of Complete the Story Game towards students’ vocabulary mastery of the fifth grade at SDN 2 Labuhan Ratu, Bandar Lampung.